Model-model Penciptaan Suasana Religius pada SMUN Kodia Malang - Muhaimin, Muhaimin; Ali, Nur; Sutiah, Sutiah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2001)
This study aims to examine how educational models create religious atmosphere in schools. This research is a concrete effort to find the right pattern to realize a religious environment in an academic context. This study uses a qualitative research approach with case study design. While the subjects in this study included a number of school principals, former principals, deputy principals, teachers and students of 4th State High School of Malang. The techniques used in data collection in this study include observations to obtain data about various teaching and learning activities, and religious activities as well as the religious atmosphere in schools as well as in-depth interviews. The implementation of religious activities in the school, which was originally